The Effect of Corporate Governance on Corporate Value: The Role of Enterprise Risk Management - Lena Sepriani; Candy Candy (Faculty of Economics and Business Udayana University, 2022)
In order to determine the effect of corporate governance on the corporate value, then moderating the relationship with enterprise risk management (ERM) is the aim of this study. This study collected secondary data from financial statements and annual reports for the 2016-2020 period of 87 companies as the sample and used panel regression as the analysis method. The results showed a significant positive effect of the audit committee on corporate value, while an independent commissioner had a significant negative effect. This study also shows no significant effect on the corporate value of managerial ownership, institutional ownership, board size, and board director. However, ERM moderated the relationship between the audit committee and corporate value and between managerial ownership and corporate value. Keyword: Corporate governance, corporate value, ERM.